Citra Partai Solidaritas Indonesia (PSI) di Generasi Milenial Kota Denpasar - Meyta Jayantri, Dsk. Gde; Purnawan, Ni Luh Ramaswati; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2019)
ABSTRACT Partai Solidaritas Indonesia (PSI – Indonesian Solidarity Party) is a new political party established in 2014. In mid-2016, PSI was declared as the only political party that passed the verification of the Ministry of Justice and Human Rights from the six parties that registered and in the fifth year it passed to 2019 Indonesian Election contesting parties. This study aims to find out the image of the PSI in the Millennial Generation of Denpasar City. The theories used in this research are Frank Jefkins Image Theory and Imagery in Politics. This research uses the descriptive quantitative method. Sampling technique in this research is purposive sampling. The analytical technique used is descriptive statistics by looking at the mean score of the PSI image. The result of this research showed that PSI image was categorized to be good because millennial had good impression and attitude, as well as high trust in the PSI. Keywords: Image, Denpasar, Millennial, PSI